The effect of hyperuricemia and its interaction with hypertension towards chronic kidney disease in patients with type 2 diabetes: evidence from a cross- sectional study in Eastern China - Chen, Xiang-yu; Lu, Feng; Zhang, Jie; Xu, Chun-xiao; Du, Xiao-fu; Liang, Ming-bin; Chen, Li-jin; Zhong, Jie-ming (Frontiers in Endocrinology, 2024)
Objectives: This study aimed to explore the synergistic interaction effect between hyperuricemia and hypertension towards chronic kidney disease in patients with type 2 diabetes.Methods: This research originates from a cross-sectional study performed in Zhejiang Province, Eastern China, between March and November 2018. The correlation between serum uric acid levels and the risk of chronic kidney disease was assessed using a restricted cubic spline model. An unconditional multivariable logistic regression model, along with an interaction table, was utilized to explore the potential interaction effect of hyperuricemia and hypertension towards chronic kidney disease.Results: 1,756 patients with type 2 diabetes were included in this study, the prevalence of chronic kidney disease (CKD) was 27.62% in this population. A U-shaped non-linear pattern emerged correlating serum uric acid (SUA) levels and CKD risk, indicating that both low and high SUA levels were linked to an increased CKD risk. This risk achieved its lowest point (nadir) at SUA approximately equals to 285μmol/L (p for trend <0.05). Once adjustments for age, gender, education level, abnormal fasting plasma glucose (FPG), abnormal hemoglobin A1c (HbA1c), abnormal total cholesterol (TC), abnormal high-density lipoprotein cholesterol (HDL-C), alcohol consumption and duration of diabetes were factored in, it was found that patients with both hyperuricemia and hypertension demonstrated a 5.42-fold (95% CI: 3.72-7.90) increased CKD risk compared to the reference group. The additive interaction between hyperuricemia and hypertension was statistically significant, as manifested by the following values: a relative excess risk due to interaction (RERI) of 2.57 (95% CI: 0.71-4.71), an attributable proportion due to interaction (AP) of 0.47 (95% CI: 0.14-0.64), and a synergy index (SI) of 2.39 (95% CI: 1.24-4.58). In contrast, there was no significant interaction effect in multiplicative scale. Conclusions:Hyperuricemia and hypertension may contribute additively to CKD, beyond their isolated impacts. Evaluating the risk of CKD in type 2 diabetes patients necessitates considering this potential interaction.